Application of fullerenes in nanomedicine: an update. (July 2013) - Dellinger, Anthony; Zhou, Zhiguo; Connor, James; Madhankumar, AB; Pamujula, Sarala; Sayes, Christie M; Kepley, Christopher L
Fullerenes are carbon spheres presently being pursued globally for a wide range of applications in nanomedicine. These molecules have unique electronic properties that make them attractive candidates for diagnostic, therapeutic and theranostic applications. Herein, the latest research is discussed on developing fullerene-based therapeutics as antioxidants for inflammatory diseases, their potential as antiviral/bacterial agents, utility as a drug delivery device and the promise of endohedral fullerenes as new MRI contrast agents. The recent discovery that certain fullerene derivatives can stabilize immune effector cells to prevent or inhibit the release of proinflammatory mediators makes them potential candidates for several diseases such as asthma, arthritis and multiple sclerosis. Gadolinium-containing endohedral fullerenes are being pursued as diagnostic MRI contrast agents for several diseases. Finally, a new class of fullerene-based theranostics has been developed, which combine therapeutic and diagnostic capabilities to specifically detect and kill cancer cells.